Implementation Of The Use Of Gamification Learning Media In Increasing Motivation For Learning Al-Qur'an Hadis At MA Ma’arif Sukorejo - Ni'mah, Maria Khoirotun; Muhtarom, Ali; Marzuki, Ahmad (Al-Ulum: Jurnal Pendidikan Islam, 2025)
The purpose of this study was to analyze how effective gamification is in attracting students' interest and motivation to learn the Qur'an Hadith. The approach taken in this study was qualitative, using observation techniques, interviews, and questionnaires to students in a high school. The findings of this study indicate that the use of gamification-based learning media has succeeded in increasing student participation in the learning process, strengthening their memory of the material, and creating a more lively and enjoyable learning atmosphere. In addition, the reward system in gamification also triggers students to be more active and involved in learning. Thus, it can be concluded that gamification is an effective approach to increasing motivation to learn the Qur'an Hadith. Therefore, educators are advised to use this method as an alternative in learning so that student learning outcomes can improve and their involvement in understanding and practicing the teachings of the Qur'an Hadith is better.